The Simultaneous Formation of Acrylamide, β-carbolines, and Advanced Glycation End Products in a Chemical Model System: Effect of Multiple Precursor Amino Acids - Chen, Cuyu; Jiao, Ye; Zeng, Maomao; He, Zhiyong; Shen, Qingwu; Chen, Jie; Quan, Wei (Frontiers in Nutrition, 2022)
This study investigated the effect of multiple precursor amino acids on the simultaneous formation of acrylamide, β-carbolines (i.e., harmane and norharmane), and advanced glycation end products (AGEs) (i.e., Nε-[carboxymethyl]lysine and Nε-[carboxyethyl]lysine) via a chemical model system. This model system was established with single or multiple precursor amino acids, including lysine–glucose (Lys/Glu), asparagine–glucose (Asn/Glu), tryptophan–glucose (Trp/Glu), and a combination of these amino acids (Com/Glu). Kinetic parameters were calculated by multiresponse nonlinear regression models. We found that the k values of the AGEs and of acrylamide decreased, while those of harmane increased in the Com/Glu model when heated to 170ºC and 200ºC. Our results indicated that the precursor amino acid of acrylamide and AGEs compete for α-dicarbonyl compounds, leading to a decrease in the formation of AGEs and acrylamide. Moreover, compared with asparagine, the precursor amino acid of β-carbolines was more likely to react with acetaldehyde by Pictet–Spengler condensation, which increased the formation of harmane and decreased the formation of acrylamide via the acrolein pathway.